PENERAPAN PENDEKATAN VISIBLE THINKING ROUTINE (VTR) BERBASIS MODEL THINK PAIR SHARE UNTUK MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA KELAS V SD INPRES GANTING KABUPATEN BANTAENG (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
English is an international language that plays a crucial role in education, technology, and communication. Vocabulary mastery is a fundamental aspect of learning English because it serves as the foundation for other language skills. However, preliminary observations at SD Inpres Ganting revealed that the vocabulary proficiency of fifth-grade students was still low. This issue stems from the use of conventional, teacher-centered learning approaches that do not train students’ reflective thinking skills. This study aims to improve students’ English vocabulary mastery through the implementation of the Visible Thinking Routine (VTR) approach based on the Think Pair Share (TPS) model. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 12 fifth-grade students of SD Inpres Ganting, Bantaeng Regency, in the second semester of the 2024/2025 academic year. Data were collected through observation, tests, and documentation, while data analysis was carried out using qualitative and quantitative techniques. The results showed an increase in teacher and student activities from the “fair” category in Cycle I to the “good” category in Cycle II. The students’ average vocabulary mastery also improved, rising from below the minimum mastery criteria (KKTP) in Cycle I to above the criteria in Cycle II. Thus, it can be concluded that the implementation of the Visible Thinking Routine (VTR) approach based on the Think Pair Share (TPS) model effectively improves the English vocabulary learning outcomes of fifth-grade students at SD Inpres Ganting, Bantaeng Regency.